Kreativitas Guru PAI dalam Menciptakan Suasana Belajar Siswa Setelah Pandemi di SMA N 1 Kec Payakumbuh - Annisa Saskia; Yulia Rahman; Fauzan Fauzan; Bambang Trisno (Universitas Maritim AMNI Semarang, 2023)
The purpose of this study is to understand the creativity of PAI teachers in creating a student learning atmosphere after the pandemic at SMA N 1 Payakumbuh District. The background of this research is that when the learning process takes place the atmosphere in the class becomes uncontrollable or noisy. Through this type of research using a qualitative approach which explains the creativity of PAI teachers in creating a student learning atmosphere after the pandemic at SMA N 1 Kec Payakumbuh. This study obtained data through interviews with class X PAI teachers who were the main data, and observations for supporting data from the interview results. The results of the study show that Islamic education teachers in class X at SMA N 1 Payakumbuh District have been creative in creating an atmosphere for student learning after the pandemic. By implementing teacher creativity in creating a learning atmosphere after the pandemic, it can realize teacher creativity in learning which aims to create a good and fun learning atmosphere after the pandemic.